Cloning of human bone morphogenetic protein-2 (hBMP-2) cDNA by PCR method - Takeda, Kohsuke; Nifuji, Akira; Maruoka, Yutaka; Tamura, Masato; Sasaki, Satoshi; Oida, Shinichiro; Iimura, Tadahiro; Enomoto, Shoji (Japanese Journal of Oral Biology, 1993)
In this study, we attempt to amplify the complementary DNAs (cDNAs) for human bone morphogenetic proteins (hBMPs), which have a strong activity of bone induction, from a cDNA library derived from a human osteosarcoma cell line MG63, using the polymerase chain reaction (PCR) method with two specific primers. Four recombinant clones, which encoded the mature region of hBMP-2, have been amplified. However, they did not contain termination codon at their 3′-terminus. PCR was performed again in order to ligate termination codon to one of the cDNAs. Sequence analysis revealed several mutations including one frameshift mutation. After elimination of the defected nucleotide moiety, a cDNA preparation encoding mature region of hBMP was obtained. It was confirmed that the amino acid sequence translated from this cDNA was identical to that of the mature region of hBMP-2.